Rempah-Rempah dalam Prasasti Warunggahan sebagai Rujukan Obat Tradisional - Alkari, Alkari; Afandi, Zainal; Setya Wiratama, Nara (Universitas Nusantara PGRI Kediri, 2024)
The background to this research is based on the results of researchers' observations which show that people now tend to choose traditional medicine in the treatment process. This phenomenon is reflected in the increasing number of consumers who buy traditional medicines, both those that are registered and those that have obtained a business license. The aim of this research is to find out what spices are contained in the Warunggahan inscription, the reasons why spices are written in the Warunggahan inscription, and the characteristics of the plants/spices in the Waunggahan inscription. In this research, researchers used a qualitative descriptive approach method. Qualitative research is research in which the discussion brings up data obtained in the field. The research was carried out in several research stages, the first was the pre-research stage in the first week of December, research implementation in January-April, data analysis in May and June, and reporting of research results in July. At the research stage, researchers conducted direct interviews, including with Novi B.M.W, Wahyu Alam and A.B Aji Setiaji. The conclusions of this research are (1) The spices contained in the Warunggahan inscription include bsar, kasumba, wunkudu, jodhi, keteke, wuyah, kamal, lena, lurunan, kletik and gula. (2) The reason for writing spices in the Warunggahan inscription is to limit the sale of goods by carrying them. (3) The plants or spices contained in the Warunggahan Inscription have the following characteristics. The leaves are serrated, thorny and non-serrated, the stems are sturdy and break easily, have fruit and a distinctive taste, can grow up to 30m, the leaves are shiny green to dark green, the fruit is hard and soft when ripe.